3-D object recognition using 2-D poses processed by CNNs and a GRNN - Polat, Ovunc; Tavsanoglu, Vedat (SPRINGER-VERLAG BERLIN, 2006)
This paper presents a novel approach to automatically recognize objects. The system used is a new model that contains two blocks; one for extracting direction and pixel features from object images using Cellular Neural Networks (CNN), and the other for classification of objects using a General Regression Neural Network (GRNN). A data set consisting of different properties of 10 different objects is prepared by CNN.
Keywords: Computer Science